2005
DOI: 10.1002/jcp.20345
|View full text |Cite
|
Sign up to set email alerts
|

Chondrocyte cluster formation in agarose cultures as a functional assay to identify genes expressed in osteoarthritis

Abstract: Understanding altered gene expression in osteoarthritic cartilage can lead to new targets for drug intervention. We established a functional assay based on chondrocyte cluster formation, a phenotype associated with osteoarthritis (OA), to screen an OA cartilage gene library. Previous reports have demonstrated that normal chondrocytes grown in suspension culture maintain their chondrocytic phenotype, however, certain growth factors such as basic fibroblast growth factor (bFGF) will induce the cells to prolifera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 39 publications
1
26
0
1
Order By: Relevance
“…Surprisingly, this antagonistic effect of bFGF does not inhibit cellular proliferation mediated by IGF-1 and/or BMP7 as was seen with PG production; rather, bFGF further promoted cellular proliferation when combined with other anabolic growth factors, leading to decreased PG production per cell and clustering of cells. Similarly, others have found bFGF to be a potent stimulator of cell cluster formation after retroviral transduction of a cDNA library in functional genomic screens for the novel mediators of OA Quintavalla et al, 2005).…”
Section: Basic Fgf (A) Actions Of Bfgf In Articular Cartilagementioning
confidence: 83%
“…Surprisingly, this antagonistic effect of bFGF does not inhibit cellular proliferation mediated by IGF-1 and/or BMP7 as was seen with PG production; rather, bFGF further promoted cellular proliferation when combined with other anabolic growth factors, leading to decreased PG production per cell and clustering of cells. Similarly, others have found bFGF to be a potent stimulator of cell cluster formation after retroviral transduction of a cDNA library in functional genomic screens for the novel mediators of OA Quintavalla et al, 2005).…”
Section: Basic Fgf (A) Actions Of Bfgf In Articular Cartilagementioning
confidence: 83%
“…In recent years, bFGF expression in osteoarthritic articular cartilage has been explored and implicated in OA development [25,27]. Previous studies also demonstrated upregulated bFGF expression in chondrocytes in human OA cartilage, which suggests that human chondrocytes can synthesise bFGF [22]. These findings prompted us to speculate that bFGF may be responsible for OA pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…OA chondrocytes at passage 1 were subjected to agarose gel culture according to the methods described by Quintavalla et al (4). Briefly, bottom agarose gel consisting of 1,300 l DMEM-Ham's F-12 containing 10% FBS and 0.8% low melt agarose (Takara Shuzo, Shiga, Japan) was cast into 6-well culture plates and then overlaid with 1,300 l of a chondrocyte suspension (5 ϫ 10 3 cells) in the same medium except for 0.4% low melt agarose at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…an effort by chondrocytes to repopulate the cartilage tissue and enhance matrix synthesis, or it could signify reversion to an earlier developmental stage of cartilage (3,4). However, little is known about the mechanisms of this phenotypic change in OA.…”
mentioning
confidence: 99%